Molecular and biophysical analysis of apoptosis using a combined quantitative phase imaging and fluorescence resonance energy transfer microscope. Issue 12 (16th August 2018) - Eldridge, Will J.; Hoballah, Jawad; Wax, Adam
Abstract : Apoptotic mechanisms are often dysregulated in cancerous phenotypes. Additionally, many anticancer treatments induce apoptosis and necrosis, and the monitoring of this apoptotic activity can allow researchers to identify therapeutic efficiency. Here, we introduce a microscope which combines quantitative phase imaging (QPI) with the ability to detect molecular events via fluorescence (or Förster) resonance energy transfer (FRET). The system was applied to study cells undergoing apoptosis to correlate the onset of apoptotic enzyme activity as observed using a FRET‐based apoptosis sensor with whole cell morphological changes analyzed via QPI. The QPI data showed changes in cell disorder strength during the initiation of apoptotic enzymatic activity. Abstract : Cancerous phenotypes often have dysregulated apoptotic pathways. Here, we introduce a microscope which combines quantitative phase imaging (QPI) with the fluorescence (or Förster) resonance energy transfer (FRET) enabled molecular sensitivity. Apoptotic activity was detected using FRET and correlated to QPI‐derived measures including optical volume and disorder strength. Cell disorder strength changed significantly during the onset of apoptosis.